(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
Declining soil fertility and limited access to synthetic fertilizers in Nigeria’s Northern Guinea Savanna necessitate sustainable alternatives for soil nutrient management. This study evaluated the effects of various animal- and plant-based organic manures on maize (Zea mays L.) yield and potassium (K) uptake. Field trials were conducted during the 2022 and 2023 cropping seasons at the National Open University of Nigeria (NOUN) Research Farm, Rigachikun, Kaduna State. Treatments included poultry droppings (POD), cow dung (COD), pig waste (PIW), groundnut shells (GNS), millet husks (MIL), rice mill waste (RMW), and a control (no manure), all applied at 10 t/ha. A randomized complete block design (RCBD) with four replications was used. Data on grain yield and K uptake were subjected to analysis of variance (ANOVA), and means were separated using the least significant difference (LSD) at p ≤ 0.05. Results showed significant yield differences among treatments. In 2022, the highest grain yield (7.90 t/ha) was from poultry droppings, while in 2023, pig waste (5.00 t/ha) outperformed other treatments. Potassium uptake followed a similar trend, with cow dung recording the highest values (33.53 kg/ha in 2022 and 29.28 kg/ha in 2023). The findings demonstrate that both animal- and plant-derived manures improve maize yield and K uptake, with poultry droppings and pig waste being the most effective. These results highlight the potential of organic manures as low-cost, sustainable inputs for restoring soil fertility and enhancing food production in the Northern Guinea Savanna.